Optimalisasi Pemanfaatan Mesin Pembuat Pelet Multifungsi Sebagai Strategi Peningkatan Produktivitas Kelompok Peternak Ikan - Nurjamiyah, Nurjamiyah; Zaharuddin, Zaharuddin; A. Ritonga, Din Aswan (Forum Kerjasama Pendidikan Tinggi, 2025)
Deli Serdang is a regency located in North Sumatra Province. Where one of the villages in Deli Serdang district is Patumbak village. Judging from the resources available in Deli Serdang, especially Patumbak Village has resources that have good potential for developing businesses. One of the businesses is a catfish farming business managed by Mr. Denianto since 2021. Based on the results of the survey that has been carried out, the proposer determines Mr. Denianto's fish farmer group as a partner. The proposer and partners agreed on several problems that have been faced by partners, including that in the production process, farmers still use factory-produced fish feed at around IDR 10,000 / kg, resulting in high production costs. This has an impact on production results, because the price of fish does not change while the price of fish feed continues to rise, so the profit of fish farmers is reduced. If farmers make their own feed, the costs incurred are smaller at around Rp. 6000/kg. This can certainly reduce the cost of expenses and increase the income of farmers. For this reason, a fish feed (pellet) making machine is needed. The high price of the machine is the main reason why partners depend on pellets to feed their livestock. Another problem is that partners do not have sufficient knowledge and skills to make quality independent feed. Another partner problem is that partners do not have access to a broad market to sell independent feed. The objectives of PKM activities are to provide socialization, training and mentoring to partners regarding: 1) making independent feed using a multifunctional machine by utilizing chicken feather waste; 2) making marketing applications so that farmers can sell independent feed to the wider community. The method of implementing the service is to provide socialization, training and mentoring to Maju Ternak Makmur Partners. The targeted results in this Community-Based Empowerment Program are Increased efficiency of the fish feed (pellet) production process with the existence of a more modern fish feed (pellet) making machine in the partner industry, so that fish farmers can make feed independently. In addition, it can also reduce farmers' operational costs, and can produce pellets in larger quantities in a shorter time. More effective product marketing methods, by making product marketing applications in the form of fish feed (pellets) and training in the use of applications as a tool in marketing products that are more clearly effective and efficient. With the training in making feed independently by utilizing chicken feather waste, partners have the knowledge to make better quality fish feed (pellets). So that it will provide an increase in income for farmers, and also improve the quality of organic fish products, reduce production costs, and not pollute the environment.